2019
DOI: 10.21203/rs.2.17991/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association studies for yield component traits in a macadamia breeding population

Abstract: Background: Breeding for new macadamia cultivars with high nut yield is expensive in terms of time, labour and cost. Most trees set nuts after four to five years, and candidate varieties for breeding are evaluated for at least eight years for various traits. Genome-wide association studies (GWAS) are promising methods to reduce evaluation and selection cycles by identifying genetic markers linked with key traits, potentially enabling early selection through marker-assisted selection. This study used 295 progen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Future work employing GS to increase genetic gain in macadamia could investigate other economically important traits, such as tree size. In the same population as the current study, O'Connor et al [18] found 16 QTLs linked with trunk circumference. The large number of markers associated with this trait, compared with other traits in the study, means that GS may be more appropriate than GWAS and MAS to increase genetic gain, given the seemingly quantitative nature of trunk circumference.…”
Section: Future Research Using Gs In Macadamiasupporting
confidence: 50%
See 1 more Smart Citation
“…Future work employing GS to increase genetic gain in macadamia could investigate other economically important traits, such as tree size. In the same population as the current study, O'Connor et al [18] found 16 QTLs linked with trunk circumference. The large number of markers associated with this trait, compared with other traits in the study, means that GS may be more appropriate than GWAS and MAS to increase genetic gain, given the seemingly quantitative nature of trunk circumference.…”
Section: Future Research Using Gs In Macadamiasupporting
confidence: 50%
“…MAS can also be conducted using genetic markers of large effect detected through genome-wide association studies (GWAS). GWAS has been conducted in macadamia for nut and kernel traits, but not for yield [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The future genetic gain is more likely from a genomics-driven breeding program which requires an in-depth understanding of all the major/minor quantitative trait loci (QTLs) segregating in the elite germplasm pools. GWAS has been found a powerful tool for dissecting complex traits by finding causative allelic variation at individual SNP markers or associated with natural phenotypic variation (Alqudah et al, 2020) which can be used effectively to fine map these traits (Garcia et al, 2019;Sheoran et al, 2019;Alqudah et al, 2020;Kumar et al, 2020;O'Connor et al, 2020;Sehgal et al, 2020). This approach has been widely used to predict phenotypically related candidate genes in many crops (Si et al, 2016;Wang et al, 2016;Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its size (>1,660 species; Christenhusz & Byng, 2016), the Proteaceae has received minimal attention from genome researchers, probably due to most diversity being restricted to the southern hemisphere as well as the nut‐producing macadamia tree being the only species within this family of significant worldwide economic interest. A genome assembly of Macadamia integrifolia has been developed (Nock et al, 2020), the information from which is used for genome‐informed breeding (O’Connor et al, 2020). Very little genetic information is available for K. exselsa ; however, karyotype analysis indicated it is a diploid species with n = 14 chromosomes (Hair & Beuzenberg, 1958).…”
Section: Introductionmentioning
confidence: 99%